CORRELATES OF LIFESTYLE AND REPRODUCTIVE HEALTH OF WOMEN WITH INFERTILITY (CAHIERS MAGELLANES-NS, 2024)
Women's lifestyle has recently aroused significant interest and has a major part in reproductive health. The habits and manner of living that can impact women's general health and well-being include fertility. This research focused on the correlation between the lifestyle and reproductive health of women who undergo infertility issues. Quantitative research was carried out. Utilizing a questionnaire, the data was collected from 120 women treated for infertility in Tirupattur District. Using statistical methods such as the 'F-test, Chi-square, Karl Pearson's Correlation, etc., the researcher analyzed the data and presented the results in tables and figures. According to this study, there was a remarkable association between the respondents’ age and their spouses’ age in reproductive health. There was a relation between the occupation and lifestyle of women with infertility. The study suggested women, change their lives healthily.